2014
DOI: 10.1111/den.12230
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of endoscopic retrograde cholangiopancreatography‐based cytology for distinguishing malignant and benign intraductal papillary mucinous neoplasm: Systematic review and meta‐analysis

Abstract: Cytology from ERCP has good specificity but poor sensitivity in distinguishing benign from malignant IPMN. Newer techniques or markers are needed to improve diagnostic yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
(81 reference statements)
0
17
0
Order By: Relevance
“…Pancreatic juice cytology during ERCP is useful for the pathological diagnosis of pancreatic neoplasms, especially those that are derived from the pancreatic duct, such as IDC (9). On the other hand, it might be difficult to diagnose a pancreatic neoplasm that is not derived from the pancreatic duct, such as a PPL, using pancreatic juice cytology.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic juice cytology during ERCP is useful for the pathological diagnosis of pancreatic neoplasms, especially those that are derived from the pancreatic duct, such as IDC (9). On the other hand, it might be difficult to diagnose a pancreatic neoplasm that is not derived from the pancreatic duct, such as a PPL, using pancreatic juice cytology.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic juice cytology (PJC) under endoscopic retrograde cholangiopancreatography (ERCP) is an examination for IPMNs, and suspicion of malignancy or positive malignancy by PJC is an absolute indication for resection. However, the sensitivity of PJC for malignant IPMN was found to be only 35% in a meta-analysis, 13 and the accuracy was also unsatisfactory (33%-64%). 2,[14][15] Furthermore, the incidence of post-ERCP pancreatitis (PEP) was also reported to be about 8%-25%.…”
Section: Ipmnmentioning
confidence: 99%
“…Assessment of pancreatic juice by a transpapillary approach is useful in the differential diagnosis of benign and malignant IPMN (Table 4). 10,[68][69][70] A meta-analysis of 13 studies that included 483 patients with IPMN found that ERCP cytology had a pooled sensitivity, specificity, and accuracy of 35.1%, 97.2%, and 92.9%, respectively, in the differential diagnosis of benign and malignant IPMN. 68 In this meta-analysis, lavage cytology improved the sensitivity to 45.8%.…”
Section: Assessment Of Pancreatic Juice By a Transpapillary Approachmentioning
confidence: 99%